Erratum to: Perturbative solutions of the f(R)-theory of gravity in a central gravitational field and some applications - Nguyen Anh Ky; Pham Van Ky; Nguyen Thi Hong Van (European Physical Journal C: Particles and Fields, 2018)
The original version of this article unfortunately contained a mistake.